2017
DOI: 10.1038/s41598-017-15130-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-jumping Mechanism of Melting Frost on Superhydrophobic Surfaces

Abstract: Frost accretion on surfaces may cause severe problems and the high-efficiency defrosting methods are still urgently needed in many application fields like heat transfer, optical and electric power system, etc. In this study, a nano-needle superhydrophobic surface is prepared and the frosting/defrosting experiments are conducted on it. Three steps are found in the defrosting process: melting frost shrinking and splitting, instantaneous self-triggered deforming followed by deformation-induced movements (namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Research related to the dynamic wettability of solid material surfaces has attracted much attention, especially for the investigation concerning the reduction of liquid–solid contact time. The ability of droplets to rapidly bounce on the surface is of great importance to industrial applications, particularly with regards to the surface with self-cleaning, anti-corrosion, and icing resistance. When a droplet impacts on a superhydrophobic surface, it will first spread to a maximum diameter on the solid surface, then retract, and finally leave the substrate or stick to it through heterogeneous surface wettability regulation. It has been reported that the contact time in the spreading stage is independent of the substrate’s microstructure or droplet’s impact velocity. In order to reduce the contact time of the droplets with the surface, shortening the contact time of droplets in the retracting stage is the key.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to the dynamic wettability of solid material surfaces has attracted much attention, especially for the investigation concerning the reduction of liquid–solid contact time. The ability of droplets to rapidly bounce on the surface is of great importance to industrial applications, particularly with regards to the surface with self-cleaning, anti-corrosion, and icing resistance. When a droplet impacts on a superhydrophobic surface, it will first spread to a maximum diameter on the solid surface, then retract, and finally leave the substrate or stick to it through heterogeneous surface wettability regulation. It has been reported that the contact time in the spreading stage is independent of the substrate’s microstructure or droplet’s impact velocity. In order to reduce the contact time of the droplets with the surface, shortening the contact time of droplets in the retracting stage is the key.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in literature which contains our own work, large amounts of surface energy can be released during the shrinking of melting frost with irregular shape, which easily triggers a self-propelled movement such as jumping. [22][23][24] As seen in Fig.3(a), the self-propelled jumping of melting frost indeed occurs very frequently (the solid circles represent original frost, the dashed circles show clean surfaces after jumping, and the white arrows indicate shadows of jumping paths). These jumping movements are able to selfremove most frost pieces, leaving an almost clean surface.…”
Section: Frost Jump Off During Defrosting When Frost Quantity Is Littlementioning
confidence: 76%
“…[18][19] Like that occurred during condensation, [20][21] self-propelled jumping, rotating and sliding movements during defrosting also take place frequently, making the defrosting process very dynamic and generating very low surface coverages on superhydrophobic surfaces. [22][23][24] On vertical superhydrophobic surfaces, the defrosting process is more efficient that the melting frost departs from the superhydrophobic surface directly at the early stage of defrosting. [25][26][27] Compared with conventional surfaces such as bare Aluminum surfaces and hydrophobic surfaces, the retention water mass or fraction presents a much lower value.…”
Section: Indroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the small gaps (spacings) between the microstructures not only enable dewetting transitions of droplets, but also promote Cassie–Baxter state frost formation, enhancing the defrosting efficiency similar to what has been observed previously. The defrosting phenomenon on nanotextured-superhydrophobic surfaces has been widely investigated, ,, concluding that the uniform nanoscale roughness promoted the Cassie–Baxter frost state, enhancing the defrosting efficiency. However, patterned square-shaped microstructures considered as hierarchical superhydrophobic surfaces cannot have confined regions.…”
Section: Resultsmentioning
confidence: 99%